Crypto Currency: An Analysis with Financial Literacy as Moderator - Sharma, Hemendra (Asian Journal of Engineering and Applied Technology, 2022)
This research paper provides a comprehensive overview on investment intention of subjects towards crypto currency. We hypothesise that trust, electronic word of mouth, perceived risk and moderator financial literacy are the primary reasons for the increased interest in crypto currencies. An online questionnaire was framed and data was collected from 247 respondents who are well aware about digital investments, possess basic knowledge of internet and are keen in exploring more digital avenues of investments. Data analysis was carried out through two stage structural equation modelling. The findings suggested that investment intentions are significantly influenced by trust, electronic word of mouth and perceived risk. Further, financial literacy moderated the effect of electronic word of mouth and trust on investment intention. The current paper is unique and first of its kind in India where it reflects the investment intentions of subjects towards crypto currency along with the linking of trust, electronic word of mouth, perceived risk and financial literacy as moderator. Particularly, the finding of this study is one of a unique attempt to make aware about the investor intention towards crypto currency for the market and the economy.